Pediatric CNS Tumor Patients Have Significantly Lower Requirement of Tissue Plasminogen Activator for Episodes of Central Venous Catheter Dysfunction Compared With Other Pediatric Oncology Patients: Results of a Population-based Cohort Study. Issue 7 (October 2020) - Howie, Chelsea; Crooks, Bruce; Moorehead, Paul; Kulkarni, Ketan
Abstract : Purpose: Central venous catheters (CVCs) are an important component of care delivery in pediatric oncology patients. However, CVC dysfunction is a common problem. Tissue plasminogen activator (tPA) is often administered to re-establish function, however, specific experience in pediatric patients with central nervous system (CNS) tumors is lacking. The goal of this study was to investigate the CVC experience and use of tPA for episodes of CVC dysfunction in pediatric patients with CNS tumors in comparison with other patients. Methods: Medical records of all pediatric oncology patients from the 4 Atlantic provinces in Canada (Nova Scotia, New Brunswick, Prince Edward Island, and Newfoundland and Labrador) were reviewed. Data collected included demographics, treatment, details of CVCs along with CVC dysfunction, and tPA use. Results: The cohort consisted of 1152 pediatric oncology patients, 222 (19.3%) of whom had CNS tumors. CVC dysfunction requiring tPA administration occurred in 12 (5.4%) of patients with CNS tumors compared with 182 (19.6%) of patients with non-CNS tumors ( P =0.0001). Multivariate logistic regression analysis showed that administration of tPA for CVC dysfunction was 2.5 times more likely in patients with non-CNS tumors than those with CNS tumors ( P =0.012; 95% confidence interval, 1.3-4.9). Conclusions: Our study showed that pediatric patients with CNS tumors require significantly less frequent administration of tPA for episodes of CVC dysfunction than patients with non-CNS tumors after adjusting for confounding factors. Hypotheses for this include: potential biologic differences of tumors, the role of the blood-brain barrier, or systematic differences in intensity of treatments.